Implementasi Imajinasi Terbimbing Untuk Mengurangi Nyeri Pada Pasien Ca Buli di Rumah Sakit Prof. Dr. Margono Soekarjo : Case Study - Milina Setianingsih; Ikit Netra (Journal of Bionursing, 2022)
Background : Bladder cancer is more common in men aged 60-70 years, infiltrative carcinoma will show symptoms of irritation from the bladder. Pain felt in bladder cancer patients is usually chronic and intermittent. Objectives: This study aims to describe nursing care and appropriate interventions in bladder cancer patients who experience pain. Methods: This research is a case study research with simple random sampling technique for sampling. This research was conducted in December 2021 with an assessment guide instrument for data collection. Researchers used the nursing care process from the assessment stage to evaluation. Result: The patient's most felt complaint was pain in the lower abdomen like being hit by a heavy object on a scale of 6, the pain came and went. Giving guided imagination intervention for 2 days was able to reduce pain to a scale of 4. Conclusion: The recommendation from this study is that nurses can provide alternatives to the use of other non-pharmacological techniques in reducing pain that can be combined with guided imagination techniques. Nurses also need to collaborate the administration of analgesics with pharmacological techniques.